Physical methods in wastewater treatment. (30th March 2011) - Kesari, Kavindra Kumar; Verma, Hriday N.; Behari, Jitendra
Physical methods of wastewater treatment are useful in water purification and recycling. We have proposed the role of nanoparticle in combination with ultrasound. Ultrasound (US), nanoparticle (NP) or in combination (US + NP) may offer an attractive proposition in the area of water purification. Ultrasound irradiation applications is that acoustic cavitation can affect a number of mechanical, acoustic, chemical and biological changes in wastewater analysis. Our present study also defines the interaction of Reactive Oxygen Species (ROS) present as contamination in wastewater during treatment process. Owing to ultrasonication and nanoparticle treatment, ROS may generate in water samples, and disrupt the bacterial cell. Number of research has been done on water purification by using ultrasound, ultraviolet and nanoparticle. Present study established the combined effect of US + NP and suggested that it may be more effective than individual. We have proposed that this may be a useful technique in water purification system.